If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -3x(5x + -17) = 3 Reorder the terms: -3x + -3x(-17 + 5x) = 3 -3x + (-17 * -3x + 5x * -3x) = 3 -3x + (51x + -15x2) = 3 Combine like terms: -3x + 51x = 48x 48x + -15x2 = 3 Solving 48x + -15x2 = 3 Solving for variable 'x'. Reorder the terms: -3 + 48x + -15x2 = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + 48x + -15x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(-1 + 16x + -5x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-1 + 16x + -5x2)' equal to zero and attempt to solve: Simplifying -1 + 16x + -5x2 = 0 Solving -1 + 16x + -5x2 = 0 Begin completing the square. Divide all terms by -5 the coefficient of the squared term: Divide each side by '-5'. 0.2 + -3.2x + x2 = 0 Move the constant term to the right: Add '-0.2' to each side of the equation. 0.2 + -3.2x + -0.2 + x2 = 0 + -0.2 Reorder the terms: 0.2 + -0.2 + -3.2x + x2 = 0 + -0.2 Combine like terms: 0.2 + -0.2 = 0.0 0.0 + -3.2x + x2 = 0 + -0.2 -3.2x + x2 = 0 + -0.2 Combine like terms: 0 + -0.2 = -0.2 -3.2x + x2 = -0.2 The x term is -3.2x. Take half its coefficient (-1.6). Square it (2.56) and add it to both sides. Add '2.56' to each side of the equation. -3.2x + 2.56 + x2 = -0.2 + 2.56 Reorder the terms: 2.56 + -3.2x + x2 = -0.2 + 2.56 Combine like terms: -0.2 + 2.56 = 2.36 2.56 + -3.2x + x2 = 2.36 Factor a perfect square on the left side: (x + -1.6)(x + -1.6) = 2.36 Calculate the square root of the right side: 1.53622915 Break this problem into two subproblems by setting (x + -1.6) equal to 1.53622915 and -1.53622915.Subproblem 1
x + -1.6 = 1.53622915 Simplifying x + -1.6 = 1.53622915 Reorder the terms: -1.6 + x = 1.53622915 Solving -1.6 + x = 1.53622915 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.6' to each side of the equation. -1.6 + 1.6 + x = 1.53622915 + 1.6 Combine like terms: -1.6 + 1.6 = 0.0 0.0 + x = 1.53622915 + 1.6 x = 1.53622915 + 1.6 Combine like terms: 1.53622915 + 1.6 = 3.13622915 x = 3.13622915 Simplifying x = 3.13622915Subproblem 2
x + -1.6 = -1.53622915 Simplifying x + -1.6 = -1.53622915 Reorder the terms: -1.6 + x = -1.53622915 Solving -1.6 + x = -1.53622915 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.6' to each side of the equation. -1.6 + 1.6 + x = -1.53622915 + 1.6 Combine like terms: -1.6 + 1.6 = 0.0 0.0 + x = -1.53622915 + 1.6 x = -1.53622915 + 1.6 Combine like terms: -1.53622915 + 1.6 = 0.06377085 x = 0.06377085 Simplifying x = 0.06377085Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.13622915, 0.06377085}Solution
x = {3.13622915, 0.06377085}
| a+12=-13 | | y=5+24 | | y=-6x^2+24x-20 | | P(x)=x^4+49x^2 | | -8x(2x-9)=20-12x | | 40+8x=-8(-5+7X) | | 3(5x+4)=x+(x-2) | | 3n+17=2 | | L=7k/3=23 | | 0.6(x+3)+1.6(x-2)= | | 3n-17=2 | | 7=4s+19 | | 3c+5-2c-7= | | -3-(-9)+4= | | 7y+6x-12= | | r^2+8r+17=0 | | (8x+1)(2x^2+13x-7)=0 | | 3.75/30 | | 0.6(x+5)+1.6(x-4)= | | (-4y+5)+5y=2 | | -4y-8y=4-32 | | 5(6x-5)=7(2x+1) | | 2(3x-5)=110 | | Y=45(6)+67 | | 0.7(x+4)+1.7(x-3)= | | 10/x=6/5x | | (x)=4e^2x | | 2(ox-7)=10 | | x/4/3=7/8 | | 0.5=2x+1 | | -6+18=7-(4x+9) | | 5x^2+2x-11= |